Making Archaeology Available to the Subaltern: Towards an Engaged, Militant Archaeology - Acuto, Felix Alejandro (2023)
Activist archaeology is certainly a small field in our discipline, and it will probably always be like this, but this does not mean that we should discard our beliefs and obligations toward the subordinate. We should keep fighting to make archaeology a more democratic, participative, plural, and engaged discipline. In my case, my praxis and archaeological militancy have been highly influenced by my relationship with Indigenous Peoples, communities, and territorial organizations in Argentina. They have taken the time to guide me and to explain their perspective about Original Peoples’ historical claims and current struggles in general and their demands on science in particular. Being in indigenous territories and learning from native wisdoms have deeply impacted my understanding ofarchaeological practice, interculturality, and political commitment.